A high entropy oxide lithium ion battery negative electrode material and its preparation method and application

By introducing Cu elements and other transition metal elements into the negative electrode materials of high-entropy oxide lithium-ion batteries, adjusting the band gap width and oxygen vacancies concentration, the problem of poor conductivity of high-entropy oxide negative electrode materials is solved, and the improvement of high energy density and excellent electrochemical performance is achieved.

CN119750665APending Publication Date: 2025-04-04TIANFU JIANGXI LAB
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411980961.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The intrinsic conductivity of the negative electrode materials of high-entropy oxide lithium-ion batteries is poor, and it is difficult to meet the needs of high energy density and excellent electrochemical performance.

Method used

By adjusting the band gap width, Cu elements and four other transition metal elements were introduced using the high-entropy lattice distortion effect, the (NiCoFeCuMn)3O4 precursor was synthesized by the high-temperature hydrothermal method, and high-entropy oxide nanoparticles with an average particle size of 300 nm were synthesized by the high-temperature sintering method.

Benefits of technology

Effectively adjust the oxygen vacancy concentration, reduce the band gap width, improve conductivity, improve electrochemical performance and cycle life, and can cycle 500 times at a current density of 0.5A/g.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750665A_ABST
    Figure CN119750665A_ABST
Patent Text Reader

Abstract

The present invention discloses a high entropy oxide negative electrode material for lithium ion batteries, and a preparation method and application thereof, and relates to the technical field of negative electrode materials for lithium batteries. A preparation method for a high entropy oxide negative electrode material for lithium ion batteries comprises the following steps: weighing a precursor, the precursor comprising Ni, Co, Fe, Cu and Mn elements; dissolving the precursor in water, stirring and dissolving to obtain solution A, adding a precipitant to solution A, mixing evenly to obtain solution B; subjecting solution B to a hydrothermal reaction, separating a supernatant and a precipitate, washing and drying the precipitate to obtain a solid precursor material; sintering the solid precursor material, and crushing it after cooling to obtain a negative electrode material. The present invention directly improves the intrinsic conductivity of the high entropy oxide negative electrode material by adjusting the band gap width, thereby further improving the electrochemical performance of the high entropy oxide negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium batteries, and in particular to a high entropy oxide negative electrode material for lithium ion batteries, a preparation method thereof and an application thereof. Background Art

[0002] In the current field of battery technology, the selection of negative electrode materials is crucial to improving the energy density, cycle stability and safety of batteries. Traditional commercial negative electrode materials, such as graphite and lithium titanate, each have significant limitations. Although graphite negative electrodes are widely used, their theoretical capacity is only 372mAh / g, their rate performance is poor, and their charge and discharge platform is too low, which can easily lead to lithium precipitation, thus causing safety problems. In contrast, although lithium titanate negative electrode materials have stress-free properties and ensure good cycle stability, their theoretical capacity is lower, only 175mAh / g, which is difficult to meet the future market demand for high energy density batteries.

[0003] In view of the shortcomings of the above materials, researchers are committed to developing new negative electrode materials in order to obtain higher theoretical specific capacity and better electrochemical reaction kinetics. In this context, high entropy negative electrode materials have attracted much attention due to their high theoretical capacity and controllable performance. The crystal structures of high entropy compound negative electrodes are diverse, including spinel, rock salt, perovskite, fluorite, wurtzite, tetragonal phase and sphalerite. Among them, the spinel structure is particularly prominent due to its unique advantages: it contains two different Wyckoff sites, which allows a wide range of valence changes during the charge and discharge process, thereby achieving high specific capacity; at the same time, the spinel structure is more thermodynamically stable, giving the negative electrode material excellent cycle performance.

[0004] In recent years, high entropy oxide anodes have been a hot topic in the research of negative electrode materials for lithium batteries, and a series of remarkable results have been achieved. For example, Bin Xiao et al. prepared (FeCoNiCrMn)3O4 negative electrode materials using high entropy alloy powders, which showed a stable structure and low band gap width. After 1200 cycles at a current density of 2A / g, the specific capacity remained at 596.5mAh / g, and the capacity retention rate was as high as 86.2%. Shun Li et al. synthesized a six-component spinel structured Zn 0.5 Co 0.5 Mn 0.5 Fe 0.5 Al 0.5 Mg 0.5 O4 negative electrode material, after 5000 cycles at a current density of 2A / g, the capacity retention rate reached 81%, and the specific capacity was stable at 290mAh / g. In addition, Zheng Sun et al. prepared (Cr 0.2 Mn 0.2 Fe 0.2Co 0.2 Ni 0.2 )3O4 electrode material, after 5000 cycles at a high current density of 5A / g, the capacity retention rate reached 100%.

[0005] However, although high entropy oxide negative electrode materials have shown great potential in performance, their intrinsic conductivity is usually poor, which is mainly attributed to the poor conductivity of general metal oxides. In order to improve this problem, researchers usually compound metal oxides with other highly conductive materials. However, there are still few reports on how to improve the intrinsic conductivity of high entropy oxide negative electrode materials. Therefore, the development of a high entropy oxide negative electrode material that has both high theoretical specific capacity and excellent electrochemical reaction kinetics and good intrinsic conductivity has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The technical problem to be solved by the present invention is the lack of a method for improving the intrinsic conductivity of high entropy oxide negative electrode materials. The purpose is to provide a high entropy oxide lithium ion battery negative electrode material and a preparation method and application thereof, and to directly improve the intrinsic conductivity of the high entropy oxide negative electrode material by adjusting the band gap width, thereby further improving the electrochemical performance of the high entropy oxide negative electrode material.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a negative electrode material for a high entropy oxide lithium-ion battery, comprising the following steps:

[0009] Weighing a precursor, the precursor includes Ni, Co, Fe, Cu and Mn elements;

[0010] Dissolve the precursor in water, stir and dissolve to obtain solution A, add a precipitant to solution A, mix well, and obtain solution B;

[0011] After subjecting solution B to a hydrothermal reaction, a supernatant and a precipitate are separated, and the precipitate is washed and dried to obtain a solid precursor material;

[0012] The solid precursor material is sintered, and then crushed after cooling to obtain the negative electrode material.

[0013] The molar ratio of Ni:Co:Cu:Fe:Mn is 0.15-0.25:0.15-0.25:0.15-0.25:0.25-0.35:0.05-0.15.

[0014] As a possible design, the above stirring dissolution is to dissolve the precursor in pure water and stir it thoroughly with a magnetic stirrer for 2 to 4 hours;

[0015] Precipitants include urea, citric acid, sodium hydroxide, potassium hydroxide and ammonia.

[0016] As a possible design, the molar ratio of the above precipitant to the sum of the elements Ni, Co, Fe, Cu and Mn is 0.5-10:1.

[0017] As a possible design, the above hydrothermal reaction is to heat solution B at 140-200°C for 6-36h.

[0018] As a possible design, the sintering is performed at 800-1400° C. in an air atmosphere for 2-12 hours.

[0019] As a possible design, the above-mentioned pulverization is to ball mill the sintered product of the solid precursor material.

[0020] As a possible design, the above-mentioned ball milling is to ball mill the sintered product of the solid precursor material at a rotation speed of 500 to 1000 rpm for 4 to 12 hours.

[0021] In a second aspect, the present invention also provides a high entropy oxide lithium-ion battery negative electrode material, which is prepared using the above method.

[0022] In a third aspect, the present invention also provides the use of a high entropy oxide lithium ion battery negative electrode material prepared by the above-mentioned preparation method in the preparation of lithium ion batteries.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] The present invention introduces Cu element with high conductivity and four other transition metal elements through the high entropy lattice distortion effect, synthesizes (NiCoFeCuMn)3O4 precursor by high temperature hydrothermal method, and then synthesizes high entropy oxide nanoparticles with an average particle size of 300nm by high temperature sintering method. The oxygen vacancy concentration can be effectively adjusted, the band gap width can be reduced, and the conductivity can be improved. Compared with the band gap of single-phase metal oxide Fe2O3, the band gap of the high entropy negative electrode material is 1.34Ev, the conductivity is increased, and the electrochemical performance is increased, and the cycle life is significantly improved, which can be cycled 500 times at a current density of 0.5A / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0026] Figure 1 is the XRD analysis diagram of the negative electrode material of Example 1;

[0027] Figure 2 This is a microscopic morphology of the negative electrode material of Example 1;

[0028] Figure 3 is a bandgap width diagram of the negative electrode material of Example 1;

[0029] Figure 4 It is a long cycle diagram of the negative electrode material of Example 1 at 0.5 A / g;

[0030] Figure 5 This is a long cycle diagram of the negative electrode material of Comparative Example 1 at 0.5 A / g;

[0031] Figure 6 This is a long cycle diagram of the negative electrode material of Comparative Example 2 at 0.5 A / g;

[0032] Figure 7 This is a long cycle diagram of the negative electrode material of Comparative Example 3 at 0.5 A / g;

[0033] Figure 8 It is a long cycle diagram of the negative electrode material of Comparative Example 4 at 0.5 A / g;

[0034] Fig. 9 It is a long cycle diagram of the negative electrode material of Comparative Example 5 at 0.5 A / g;

[0035] Fig.10 This is a diagram of the band gap width of the negative electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0037] A method for preparing a negative electrode material for a high entropy oxide lithium-ion battery comprises the following steps:

[0038] S1. Weigh the precursor, which includes Ni, Co, Fe, Cu and Mn elements.

[0039] Determining the content of each element makes it easier to control the composition of the negative electrode material.

[0040] In some embodiments of the present invention, the molar ratio of Ni:Co:Cu:Fe:Mn is 0.15-0.25:0.15-0.25:0.15-0.25:0.25-0.35:0.05-0.15.

[0041] The inventors have found that under this ratio, the various elements in the high entropy oxide can play a better synergistic role, reduce the band gap width as much as possible, and improve the conductive performance.

[0042] Preferably, the molar ratio of Ni:Co:Cu:Fe:Mn is 0.2:0.2:0.2:0.3:0.1.

[0043] Preferably, the above-mentioned precursors include but are not limited to nitrates, sulfates and carbonates.

[0044] S2. Dissolve the precursor in water, stir to dissolve, obtain solution A, add a precipitant to solution A, mix well, and obtain solution B.

[0045] The metal salts are mixed evenly to facilitate a fully uniform reaction in the subsequent steps.

[0046] In some embodiments of the present invention, the stirring dissolution is to dissolve the precursor in pure water and stir it thoroughly with a magnetic stirrer for 2 to 4 hours.

[0047] In some embodiments of the present invention, the precipitant includes urea, citric acid, sodium hydroxide, potassium hydroxide and ammonia water.

[0048] In some embodiments of the present invention, the molar ratio of the above precipitant to the sum of the elements Ni, Co, Fe, Cu and Mn is 0.5-10:1.

[0049] S3. After subjecting solution B to a hydrothermal reaction, the supernatant and the precipitate are separated, and the precipitate is washed and dried to obtain a solid precursor material.

[0050] Through a hydrothermal reaction, the metal ions are allowed to fully react with the precipitant at high temperature to form a complex precipitate or a hydroxide precipitate, and then the solid precursor material is separated.

[0051] In some embodiments of the present invention, the hydrothermal reaction is to heat solution B at 140-200° C. for 6-36 hours.

[0052] Preferably, the solution B is placed in a 200 mL hydrothermal kettle for reaction.

[0053] Preferably, the above-mentioned precipitate cleaning is specifically to use deionized water and anhydrous ethanol to clean the precipitate in sequence, and each cleaning is first stirred, washed, and filtered, and the process of cleaning with deionized water and anhydrous ethanol is repeated 3 times.

[0054] Preferably, the drying is carried out at 80-120°C.

[0055] S4, sintering the solid precursor material, and crushing it after cooling to obtain the negative electrode material.

[0056] Through sintering, the solid precursor material is sintered at high temperature to form a spinel phase, and then the particle size of the high entropy oxide powder is reduced and the uniformity is improved through ball milling.

[0057] In some embodiments of the present invention, the sintering is performed at 800-1400° C. in an air atmosphere for 2-12 hours.

[0058] In some embodiments of the present invention, the pulverization is ball milling of the sintered product of the solid precursor material.

[0059] In some embodiments of the present invention, the ball milling is to ball mill the sintered product of the solid precursor material at a rotation speed of 500 to 1000 rpm for 4 to 12 hours.

[0060] Preferably, the mass ratio of the zirconium beads to the sintered product of the solid precursor material is 2:0.8-1.2.

[0061] Preferably, sieving is performed after crushing.

[0062] The present invention also provides a high entropy oxide lithium ion battery negative electrode material, which is prepared by the above method.

[0063] The present invention also provides the use of a high entropy oxide lithium ion battery negative electrode material prepared by the above-mentioned preparation method in the preparation of lithium ion batteries.

[0064] Example 1

[0065] A method for preparing a negative electrode material for a high entropy oxide lithium-ion battery comprises the following steps:

[0066] S1. Calculate and weigh the metal salt precursor (nitrate / sulfate / carbonate) according to the molar ratio of Ni:Co:Cu:Fe:Mn=0.2:0.2:0.2:0.3:0.1;

[0067] S2. Use a 100 mL beaker to take pure water, place the nitrate / sulfate / carbonate precursor in the pure water, use a magnetic stirrer to fully stir for 2 hours to obtain solution A, add a precipitant (urea) to solution A, the molar ratio of the precipitant to the metal element is in the range of 5, mix well, and obtain solution B;

[0068] S3. Place the completely dissolved solution B in a 200mL / 500mL hydrothermal autoclave, and prepare the reaction in a heating box at a heating temperature of 170°C for 24 hours. After the furnace is cooled to room temperature, take it out, pour out the supernatant in the hydrothermal autoclave, take out the precipitate in the hydrothermal autoclave and place it in a beaker; use anhydrous ethanol / pure water to stir, wash, and filter, repeat the process 3 times, and dry it in a drying oven at 100°C to finally obtain a solid precursor material.

[0069] S4. The solid material is placed in a muffle furnace, in an air atmosphere, and sintered at 1200°C for 6 hours. The furnace is then cooled to room temperature and taken out. The sintered high entropy oxide material is placed in a ball mill for ball milling. The mass ratio of zirconium beads to precursor is 2:1. The ball milling time is 8 hours and the rotation speed is 800 rpm. The fine powder is sieved out with a sieve to obtain the negative electrode material.

[0070] Example 2

[0071] A method for preparing a negative electrode material for a high entropy oxide lithium-ion battery comprises the following steps:

[0072] S1. Calculate and weigh the metal salt precursor (nitrate / sulfate / carbonate) according to the molar ratio of Ni:Co:Cu:Fe:Mn=0.15:0.25:0.2:0.25:0.15;

[0073] S2. Use a 100 mL beaker to take pure water, place the nitrate / sulfate / carbonate precursor in the pure water, use a magnetic stirrer to fully stir for 2 hours to obtain solution A, add a precipitant (urea) to solution A, the molar ratio of the precipitant to the metal element is in the range of 0.5, mix well, and obtain solution B;

[0074] S3. Place the completely dissolved solution B in a 200mL / 500mL hydrothermal autoclave, and prepare the reaction in a heating box at a heating temperature of 140°C for 6 hours. After the furnace is cooled to room temperature, take it out, pour out the supernatant in the hydrothermal autoclave, take out the precipitate in the hydrothermal autoclave and place it in a beaker; use anhydrous ethanol / pure water to stir, wash, and filter, repeat the process 3 times, and dry it in a drying oven at 80°C to finally obtain a solid precursor material.

[0075] S4. The solid material is placed in a muffle furnace, sintered at 800°C for 2 hours in an air atmosphere, and then the furnace is cooled to room temperature and taken out. The sintered high entropy oxide material is placed in a ball mill for ball milling. The mass ratio of zirconium beads to precursor is 2:0.8. The ball milling time is 4 hours and the rotation speed is 500 rpm. The fine powder is sieved out with a sieve to obtain the negative electrode material.

[0076] Example 3

[0077] A method for preparing a negative electrode material for a high entropy oxide lithium-ion battery comprises the following steps:

[0078] S1. Calculate and weigh the metal salt precursor (nitrate / sulfate / carbonate) according to the molar ratio of Ni:Co:Cu:Fe:Mn=0.25:0.15:0.25:0.35:0.05;

[0079] S2. Use a 100 mL beaker to take pure water, place the nitrate / sulfate / carbonate precursor in the pure water, use a magnetic stirrer to fully stir for 4 hours to obtain solution A, add a precipitant (urea) to solution A, the molar ratio of the precipitant to the metal element is in the range of 10, mix well, and obtain solution B;

[0080] S3. Place the completely dissolved solution B in a 200mL / 500mL hydrothermal autoclave, and prepare the reaction in a heating box at a heating temperature of 200°C for 36 hours. After the furnace is cooled to room temperature, take it out, pour out the supernatant in the hydrothermal autoclave, take out the precipitate in the hydrothermal autoclave and place it in a beaker; use anhydrous ethanol / pure water to stir, wash, and filter, repeat the process 3 times, and dry it in a drying oven at 120°C to finally obtain a solid precursor material.

[0081] S4. The solid material is placed in a muffle furnace and sintered at 1400°C for 12 hours in an air atmosphere. The furnace is then cooled to room temperature and taken out. The sintered high entropy oxide material is placed in a ball mill for ball milling. The mass ratio of zirconium beads to precursor is 2:1.2. The ball milling time is 12 hours and the rotation speed is 1000 rpm. The fine powder is sieved out with a sieve to obtain the negative electrode material.

[0082] Example 4

[0083] A method for preparing a negative electrode material for a high entropy oxide lithium-ion battery comprises the following steps:

[0084] S1. Calculate and weigh the metal salt precursor (nitrate / sulfate / carbonate) according to the molar ratio of Ni:Co:Cu:Fe:Mn=0.2:0.2:0.2:0.35:0.1;

[0085] S2. Use a 100 mL beaker to take pure water, place the nitrate / sulfate / carbonate precursor in the pure water, use a magnetic stirrer to fully stir for 4 hours to obtain solution A, add a precipitant (citric acid) to solution A, the molar ratio of the precipitant to the metal element is in the range of 10, mix well, and obtain solution B;

[0086] S3. Place the completely dissolved solution B in a 200mL / 500mL hydrothermal autoclave, and prepare the reaction in a heating box at a heating temperature of 180°C for 26 hours. After the furnace is cooled to room temperature, take it out, pour out the supernatant in the hydrothermal autoclave, take out the precipitate in the hydrothermal autoclave and place it in a beaker; use anhydrous ethanol / pure water to stir, wash, and filter, repeat the process 3 times, and dry it in a drying oven at 90°C to finally obtain a solid precursor material.

[0087] S4. The solid material is placed in a muffle furnace and sintered at 1300°C for 11 hours in an air atmosphere. The furnace is then cooled to room temperature and taken out. The sintered high entropy oxide material is placed in a ball mill for ball milling. The mass ratio of zirconium beads to precursor is 2:1. The ball milling time is 7 hours and the rotation speed is 700 rpm. The fine powder is sieved out with a sieve to obtain the negative electrode material.

[0088] Comparative Example 1

[0089] This comparative example is basically the same as Example 1, except that: Ni:Co:Cu:Fe:Mn=0.1:0.2:0.2:0.3:0.1.

[0090] Comparative Example 2

[0091] This comparative example is substantially the same as Example 1, except that Mn is missing.

[0092] Comparative Example 3

[0093] This comparative example is basically the same as Example 1, except that the sintering temperature is 600°C.

[0094] Comparative Example 4

[0095] This comparative example is basically the same as Example 1, except that the sintering temperature is 1600°C.

[0096] Comparative Example 5

[0097] This comparative example is basically the same as Example 1, except that the hydrothermal reaction temperature is 120°C.

[0098] Experimental example

[0099] Electrode sheets were prepared using the negative electrode materials of Example 1 and Comparative Examples 1-5, respectively, and electrical performance tests were performed.

[0100] (I) Specific capacity after 500 cycles

[0101] Preparation of electrode sheets: The prepared high entropy oxide negative electrode material was fully ground with polyvinylidene fluoride (PVDF) and acetylene black according to a ratio of 7:2:1, wherein PVDF was dissolved in N-methylpyrrolidone solvent (to form a solution with a mass fraction of 30%) to form a uniform slurry. A 100 μm electrode sheet was prepared by a coating process, and the electrode sheet was cut into a disc with a diameter of 12 mm.

[0102] Button cell assembly: The electrode sheets in step 9 were assembled into lithium-ion button cells in a glove box under an argon atmosphere.

[0103] The specific capacity of the battery after 500 cycles was obtained by testing with the Blue Electric test system. The results are shown in Table 1.

[0104] Table 1

[0105] Sample Specific capacity (mAh / g) Example 1 447 Comparative Example 1 344 Comparative Example 2 150 Comparative Example 3 130 Comparative Example 4 330 Comparative Example 5 284

[0106] It can be seen from Table 1 that the specific capacity of the battery in Example 1 is the best. By comparing Example 1 with Comparative Example 1, it can be seen that the ratio of Ni:Co:Cu:Fe:Mn can improve the battery performance within .15~0.25:0.15~0.25:0.15~0.25:0.25~0.35:0.05~0.15, and the battery performance is best when Ni:Co:Cu:Fe:Mn=0.25:0.15:0.25:0.35:0.05. By comparing Example 1 with Comparative Examples 1-2, it can be seen that when the Mn element is missing, the battery specific capacity is only 150, while when Ni, Co, Cu, Fe and Mn are all present, the specific capacity is as low as 344, which shows that the combination of each element of Ni, Co, Cu, Fe and Mn can play a better synergistic role, reduce the band gap width and improve the conductivity. Comparative Example 1 and Comparative Examples 3-4 show that a sintering temperature that is too low will result in a low specific capacity of only 130, which may be due to the failure to reach the required sintering temperature and the failure of the solid precursor material to sinter at high temperature to form a spinel phase; while a sintering temperature that is too high will also result in a low specific capacity, which may be due to the excessive sintering temperature affecting the formation of the spinel phase. Comparative Example 1 and Comparative Example 5 show that the battery specific capacity obtained by the low hydrothermal reaction temperature is only 284, which may be due to the insufficient temperature causing the metal ions to not fully react with the precipitant to form a precipitate.

[0107] (II) Specific capacity of different number of cycles

[0108] The specific capacity of the batteries made of the negative electrode materials of Example 1 and Comparative Examples 1-5 after 0, 100, 200, 300, 400 and 500 cycles of long cycles were obtained by testing with a blue electric test system. Figure 4-9 shown.

[0109] Figure 4 This is a long cycle diagram of the negative electrode material of Example 1 at 0.5A / g. Figure 4 After 500 cycles, the specific capacity of the negative electrode material is 447 mAh / g and the coulombic efficiency is 97%.

[0110] Figure 5 This is a long cycle diagram of the negative electrode material of Comparative Example 1 at 0.5A / g. Figure 5 After 500 cycles, the specific capacity of the negative electrode material is 344 mAh / g.

[0111] Figure 6 This is a long cycle diagram of the negative electrode material of Comparative Example 2 at 0.5A / g. Figure 6 The specific capacity of the negative electrode material is 150 mAh / g after 500 cycles.

[0112] Figure 7 This is a long cycle diagram of the negative electrode material of Comparative Example 3 at 0.5A / g. Figure 7 The specific capacity of the negative electrode material is 130 mAh / g after 500 cycles.

[0113] Figure 8 This is a long cycle diagram of the negative electrode material of Comparative Example 4 at 0.5A / g. Figure 8 The specific capacity of the negative electrode material is 330 mAh / g after 500 cycles.

[0114] Fig. 9 This is a long cycle diagram of the negative electrode material of Comparative Example 5 at 0.5 A / g. Fig. 9 The specific capacity of the negative electrode material is 284 mAh / g after 500 cycles.

[0115] Observation 4-9 shows that Example 1 ( Figure 4 ) has the best specific capacity.

[0116] (III) Analysis of negative electrode materials of Example 1

[0117] Figure 1 This is the XRD analysis diagram of the negative electrode material of Example 1. Figure 1 All XRD diffraction peaks are consistent with those of the standard card POF#75-0049, and there are no other impurity peaks, indicating that pure spinel Fd-3m(227) high entropy oxide has been successfully synthesized.

[0118] Figure 2 This is a microscopic morphology of the negative electrode material of Example 1. Figure 2 From the microscopic morphology diagram in the figure, it can be concluded that the average particle size of the negative electrode material is 300nm.

[0119] Figure 3is a graph showing the band gap width of the negative electrode material of Example 1. Figure 3 The position where the tangent line of the ultraviolet diffuse reflectance data intersects with the abscissa can indicate that the band gap width of the negative electrode material is 1.34 eV.

[0120] Fig.10 Figure 2 is a graph showing the band gap width of the negative electrode material of Comparative Example 1. Fig.10 The position where the tangent line of the ultraviolet diffuse reflectance data intersects with the abscissa can indicate that the band gap width of the negative electrode material is 2.69 eV.

[0121] contrast Figure 3 and Fig.10 It can be seen that the negative electrode material prepared by the method of the present invention has a smaller band gap width, so the negative electrode material can have higher intrinsic conductivity.

[0122] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material for a high entropy oxide lithium-ion battery, characterized in that: The steps include: Weighing a precursor, the precursor includes Ni, Co, Fe, Cu and Mn elements; Dissolve the precursor in water, stir and dissolve to obtain solution A, add a precipitant to solution A, mix well, and obtain solution B; After subjecting solution B to a hydrothermal reaction, a supernatant and a precipitate are separated, and the precipitate is washed and dried to obtain a solid precursor material; The solid precursor material is sintered, and then crushed after cooling to obtain the negative electrode material.

2. The method for preparing a high entropy oxide negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The molar ratio of Ni:Co:Cu:Fe:Mn is 0.15-0.25:0.15-0.25:0.15-0.25:0.25-0.35:0.05-0.

15.

3. The method for preparing a high entropy oxide lithium-ion battery negative electrode material according to claim 1, characterized in that: The stirring dissolution is to dissolve the precursor in pure water and stir it thoroughly for 2 to 4 hours with a magnetic stirrer; The precipitating agent includes urea, citric acid, sodium hydroxide, potassium hydroxide and ammonia water.

4. The method for preparing a negative electrode material for a high entropy oxide lithium-ion battery according to claim 1, characterized in that: The molar ratio of the precipitant to the elements Ni, Co, Fe, Cu and Mn is 0.5-10:

1.

5. The method for preparing a high entropy oxide negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The hydrothermal reaction is to heat solution B at 140-200° C. for 6-36 hours.

6. The method for preparing a high entropy oxide negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The sintering is carried out at 800-1400° C. in an air atmosphere for 2-12 hours.

7. The method for preparing a high entropy oxide lithium-ion battery negative electrode material according to claim 1, characterized in that: The pulverization is to ball-mill the sintered product of the solid precursor material.

8. The method for preparing a negative electrode material for a high entropy oxide lithium-ion battery according to claim 7, characterized in that: The ball milling is to ball mill the solid precursor material sintered product at a rotation speed of 500 to 1000 rpm for 4 to 12 hours.

9. A high entropy oxide lithium ion battery negative electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of a high entropy oxide lithium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 8 in the preparation of lithium ion batteries.

Citation Information

Cited By

  • High-entropy oxide catalyst as well as preparation method and application thereof

    CN122352368A